Factors associated with the failure of first and second-line antiretroviral therapies therapy, a case control study in Cambodian HIV-1 infected children - Barennes, Hubert (BMC Res Notes, 2016)
BACKGROUND: Little is known about the efficacy of first and and second-line antiretroviral therapies (ART) for HIV-1 infected children in resource limited Southeast Asian settings. Previous studies have shown that orphans are at a higher risk for virological failure (VF) in Cambodia. Consequently most of them required transfer to second-line ART. We assessed the factors associated with VF among HIV-1 infected children who were either under first-line (mostly 3TC + D4T + NVP) or under second-line (mostly ABC + DDI + LPV) therapies at a referral hospital in Cambodia. METHODS: A case-control study was conducted from February to July 2013 at the National Pediatric Hospital among HIV-1 infected children (aged 1–15 years) under second-line ART (cases) or first-line (matched controls at a ratio of 1:3) regimens. Children were included if a HIV-1 RNA plasma viral load (VL) result was available for the preceding 12 months. A standardized questionnaire explored family sociodemographics, HIV history, and adherence to ART. Associations between VF (HIV-1 RNA levels ≥1000 copies/ml) and the children’s characteristics were assessed using bivariate and multivariate analyses. RESULTS: A total of 232 children, 175 (75.4 %) under first-line and 57 (24.6 %) under second-line ART, for a median of 72.0 (IQR: 68.0–76.0) months, were enrolled. Of them, 94 (40.5 %) were double orphans and 51 (22.0 %) single orphans, and 77 (33.2 %) were living in orphanages. A total of 222 children (95.6 %) were deemed adherent to ART. Overall, 18 (7.7 %; 95 % CI 4.6–11.9) showed a VF, 14 (8.6 %; 95 % CI 4.8–14.0) under first-line and 4 (7.0 %; 95 % CI 1.9–17.0) under second-line ART (p = 0.5). Their median CD4 percentage was 8 % (IQR 2.9–12.9) at ART initiation. Children under second-line ART were older; more often double orphans, and had lower CD4 cell counts at the last control. In the multivariate analysis, having the last CD4 percentage below 15 % was the only factor associated with VF for ART regimen separately or when combined (OR 40.4; 95 % CI 11–134). CONCLUSIONS: The pattern of risk factors for VF in children is changing in Cambodia. Improved adherence evaluation and intensified monitoring of children with low CD4 counts is needed to decrease the risk of VF. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13104-016-1884-y) contains supplementary material, which is available to authorized users.